Characterization and shelf-life study of functional yoghurt based oral strip in polypropylene–aluminium/LLDPE blister pack - Abdul Kalam Saleena, Lejaniya; Lin, Nyam Kar; Yusof, Yus Aniza; Song, Adelene Ai Lian; Lionel, Lian Au In; Pui, Liew Phing (Springer, 2024)
This study focuses on the development of a functional yoghurt oral flm strip with antibacterial properties and probiotics [(Streptococcus thermophilus (S. thermophilus), Lactobacillus bulgaricus (L. bulgaricus), and Lactococcus cremoris (L. cremoris)] using a pectin/glycerol mixture. The tensile characters, colour, physiochemical characters, in vitro disintegration time, mouth dissolving time and in vitro dissolution test of the functional yoghurt oral strip was compared with commercial oral strips. The study examined the storage stability of functional yogurt oral strips over a period of 35 days at room temperature (25 °C) using blister packs made of polypropylene/aluminium and polypropylene/linear low-density polyethylene (LLDPE). Signifcant changes in mechanical properties, colour, surface pH, in vitro disintegration, and mouth dissolving time was observed with in vitro dissolution time of 6 min. Functional oral strip showed signifcant (p<0.05) reduction in surface pH and probiotic viability, along with a signifcant increase in mouth dissolving time during storage in both packaging materials. Developed functional yoghurt oral strip also demonstrated better antibacterial quality on both storage materials with similar in vitro dissolution time periods. A satisfactory probiotic viability (>6 log CFU/strip) was upheld for 28 days in a polypropylene/aluminium blister pack, resulting in an extended shelf life for the functional yogurt oral strip. Therefore, this functional yoghurt oral strip development can be considered as a promising production method to retain functional qualities with longer shelf life at room temperature.